The Decision Phases Framework for Public Engagement: Engaging Stakeholders about Gene Editing in the Wild - Barnhill-Dilling, S. Kathleen (The Hastings Center report, 2021)
Some experts and advocates propose environmental biotechnologies such as genetic engineering, gene drive systems, and synthetic biology as potential solutions to accelerating rates of species loss. While these tools may offer hope for a seemingly intractable problem, they also present potential governance challenges for which innovative decision-making systems are required. Two of the perennial governance challenges include, when are broader stakeholder groups involved in these decisions and who exactly should be involved? We propose the decision phases framework—which includes research and development, regulatory review, and deployment, management, and monitoring—as a framework for identifying which stakeholders might be best suited for different phases throughout the innovation and deployment of emerging environmental biotechnologies for species protection.